State substitution for the trade union good: the case of paid holiday entitlements - Forth, John; Bryson, Alex (Bonn, 2018)
"The literature on the union wage premium is among the most extensive in labour economics but unions' effects on other aspects of the wage-effort bargain have received much less attention. We contribute to the literature through a study of the union premium in paid holiday entitlements, using large-scale survey data for the UK. We find that the union premium on paid holidays is substantially larger than the union premium on wages. However, the premium fell with the introduction of a statutory minimum entitlement to paid leave. This is indicative of the difficulties that unions have faced in protecting the most vulnerable employees, and symptomatic of their decreasing regulatory role in the UK labour market."